On the significance of the different geometrical and dosimetric parameters in microbeam and minibeam radiation therapy a retrospective evaluation - McGarrigle, Josie May; Long, Kenneth Richard; Prezado, Yolanda (Frontiers in Oncology, 2024)
IntroductionSpatially Fractionated Radiation Therapy (SFRT) is an unconventional therapeutic approach with the potential to disrupt the classical paradigms of conventional radiation therapy. The high spatial dose modulation in SFRT is believed to activate distinct radiobiological mechanisms which lead to remarkable increases in normal tissue tolerance. To make optimal use of SFRT and its benefits, a deeper understanding of the biological response and its relationship with the complex dosimetric and geometric components of SFRT is essential.MethodA retrospective evaluation of preclinical studies was conducted to gain insight into the dosimetric and geometric parameters that are most correlated with normal tissue response. Current literature evaluates the response of tissue to MBRT and MRT according to various end points, e.g. the level of desquamation, degree of necrosis, or the amount of malcalcification. A set of metrics was developed to allow a quantitative comparison of these results.ResultsThe strongest correlations were observed with the doses in both the peaks and valleys as well as the ratio of the area covered by the peak over the total area. This emphasises the geometry of the beam. MBRT challenged previous uniform dose-distribution paradigms by highlighting the critical role of Peak Dose alongside Valley Dose in tissue sparing whereas MRT underscores the significant influence of geometric beam parameters on tissue preservation.DiscussionThe data exhibits variability in the results obtained using different animal models and endpoints and additional research is warranted to explore the trends observed in this study under controlled conditions.